Integrative Curriculum Framework for Practical Qur’anic-Based Educational Economic Development - Iskandar Iskandar; Materan Materan; Nur Syamsi (JURNAL ISLAM NUSANTARA, 2025)
This study examines the implementation and impact of a Qur’an-based integrated curriculum in strengthening Islamic financial literacy among santri in a pesantren within a Muslim minority context. The separation between Islamic ethical teachings and everyday economic practices has contributed to financial vulnerability, consumptive behavior, and weak ethical decision-making among Muslim youth, particularly where access to Islamic financial institutions is limited. Using a qualitative Participatory Action Research (PAR) design, data were collected through observations, interviews, focus group discussions, pre- and post-tests, and documentation, and were analyzed thematically with methodological triangulation. The findings reveal three key results. First, students demonstrated low Islamic financial literacy, marked by ritualistic understanding, the normalization of debt, and susceptibility to social media–driven consumerism. Second, the Qur’an-based integrated learning model effectively enhanced students’ conceptual clarity and ethical awareness by connecting scriptural values, reflective practices, and contextual economic cases. Third, the intervention produced sustained transformations in values, attitudes, and behaviors, including ethical caution toward debt, responsible financial choices, and adaptive community-based economic strategies. The study contributes theoretically by translating the unity of knowledge into applied curriculum practice and practically by offering a replicable model for pesantren-based economic empowerment. Future studies should employ longitudinal designs to assess the durability of behavioral change.